Influence of Salmonella status on the long‐term outcome of horses after colic surgery*. Issue 6 (29th April 2017) - Southwood, Louise L.; Lindborg, Susan; Myers, Marc; Aceto, Helen W.
Abstract: Objective: To compare long‐term outcome of Salmonella ‐positive versus Salmonella ‐negative horses discharged from hospital after colic surgery. Study design: Retrospective case‐control. Animals: Horses discharged from the hospital after colic surgery. For each horse with positive culture for Salmonella enterica (SAL‐POS, n = 59), at least 2 horses testing negative for S. enterica (SAL‐NEG, n = 119) were enrolled. Methods: Owners were interviewed via phone at least 12 months after surgery regarding: (1) complications after discharge from the hospital; (2) duration of survival; and (3) return to prior or intended use. Association between immediate postoperative clinical variables such as Salmonella status and long‐term measures of outcome was tested via ratios (odds ratio [OR]) and 95% confidence intervals. Data were analyzed for survival using a Cox proportional hazards model and for return to use using multivariable logistic regression. Results: SAL‐POS horses had a higher OR of surgical site infection (2.7 [1.1‐6.9] P = .027) and weight loss (6.8 [1.8‐26.1] P = .002). At the time of follow‐up, there were 53/56 (95%) SAL‐POS and 99/118 (84%) SAL‐NEG horses alive. The final multivariable model for nonsurvival included postoperative colic (hazard ratio 7.6 [2.8‐19.2] P = .002) and the interaction between Salmonella status and duration of rectal temperature > 103°F postoperatively (SAL‐POS 1.04 [1.01‐1.07] and SAL‐NEG 1.16 [1.06‐1.25], P = .005). The majority of horses returned to their intended use regardless of their SAL‐POS (38/50, 76%) or SAL‐NEG (77/96, 80%, P = .498) status. Conclusion: Salmonella ‐positive horses that survive to discharge from the hospital after colic surgery have similar risks of long‐term complications (colic/diarrhea), survival, and return to function than Salmonella ‐negative horses.